The Impact of the COVID-19 Pandemic on the Volume of Mammograms in Brazil: a Forecast Analysis Based on Historical Numbers - Demarchi, Patrícia Kellen Haboski (2022)
Introduction: Breast cancer is the leading cause of death by cancer in Brazilian women. Data on the real impact of the pandemic on breast cancer screening and diagnosis policy in Brazil are still unknown. Objective: Evaluate the effect of the COVID-19 pandemic on the number of mammograms performed in the Brazilian Unified Health System (SUS). Method: Epidemiological, quantitative, cross-sectional study. Monthly mammograms performed at SUS through the Department of Informatics of the SUS (DATASUS) were selected. The historical volume from January 2017 to March 2020, the month following the first case of COVID-19 diagnosed in Brazil, was evaluated to build a forecast model of expected mammograms from March 2020 to December 2021. Result: In 2020, 1,705,475 mammograms were not performed compared to the previous year, according to DATASUS. The prediction model, based on historical values, showed a deficit of 1,635,420 mammograms. In May 2020, there was the biggest drop of the exams, representing only 20.69% of mammograms performed in the same month of the previous year. Conclusion: Early detection of breast cancer was one of the medical areas impacted by the restrictions and social distance policy imposed in 2020. In this sense, future government efforts will be needed to offer treatment to potential patients with late diagnosis of breast cancer, in addition to the mammograms that were not done.